Thermal Comfort Analysis To Achieve Solemnity In Worship At The Pathok Negoro Plosokuning Mosque Yogyakarta - Ayuningtyas, Nurina Vidya; Diaz, Joseph; Kindi, Kindi (Jurnal RAUT, 2025)
The mosque is a place of worship for Muslims which is used as a building to perform worship. Therefore, many factors must be planned in the process of planning a good house of worship. This function is none other than because worship is a vertical relationship with Allah SWT. So one of the main factors that must be considered is comfort in performing prayers to support devotion in performing worship. In this study, the study is specifically aimed at examining thermal comfort in the Pathok Negoro Mosque building in Plosokuning in Minomartani, Sleman Regency. The research method used is the interview method, literacy studies and measurements using tools on the object of study. Interviews are used to obtain data from the surrounding community who usually use the Pathok Negoro Mosque, which then the results of the interviews are checked using tools in numerical units. The results of this study prove that the level of thermal comfort in the Pathok Negoro Plosokuning Mosque reaches a temperature value below the maximum standard set by SNI 03-6572-2001, which is below 25 c.